2023
DOI: 10.3390/molecules28041599
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability of Cottonseed Butter Products under Accelerated Storage Conditions

Abstract: Cottonseed is a natural product of cotton (Gossypium spp.) crops. This work evaluated the oxidative stability of cottonseed butters through accelerated autoxidation by storage at 60 °C for 25 days. Three oxidative stability parameter values (peroxide value, p-anisidine value, and total oxidation value) were monitored over the storage time. These chemical measurements revealed that the storage stability of the butter products was dominated by primary oxidation of lipid (oil) components, while the secondary oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The elevated storage temperature prompted a reduction in levels of C18:1, C18:2, and C18:3 in PSO, blend, and SL regardless of the presence of antioxidants. A similar reduction in PUFA was reported in a previous study where butter was prepared from cottonseed oil and stability was assessed under an accelerated storage study . The incorporation of RE aided in the retention of unsaturated fatty acids during accelerated storage, such as C18:1, C18:2, and C18:3.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The elevated storage temperature prompted a reduction in levels of C18:1, C18:2, and C18:3 in PSO, blend, and SL regardless of the presence of antioxidants. A similar reduction in PUFA was reported in a previous study where butter was prepared from cottonseed oil and stability was assessed under an accelerated storage study . The incorporation of RE aided in the retention of unsaturated fatty acids during accelerated storage, such as C18:1, C18:2, and C18:3.…”
Section: Resultssupporting
confidence: 65%
“…A similar reduction in PUFA was reported in a previous study where butter was prepared from cottonseed oil and stability was assessed under an accelerated storage study. 53 The incorporation of RE aided in the retention of unsaturated fatty acids during accelerated storage, such as C18:1, C18:2, and C18:3. It was observed that the effectiveness of RE in the retention of unsaturated fatty acids was superior to BHT.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation procedure was modified as per previous reports [28,29]. The butter products were formulated with four ingredients, that is, roasted Gl cottonseed kernels (oil consent 35.0%), external cottonseed oil, table salt and cane sugar.…”
Section: Cottonseed Butter Preparationmentioning
confidence: 99%
“…In our research efforts, we have evaluated the impact of the roasting temperature (from 110 to 150 • C) on the chemical profiles of extractable components of cottonseed kernels [27]. Based on the results, we have completed the initial formulation of peanut butter-like products from Gl cottonseed kernels and evaluated their oxidative stability under accelerated storage conditions [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas cottonseed is a natural resource of agrochemicals (e.g., fiber, proteins, carbohydrates, and lipids), its nutritional value is hindered by the presence of a toxic chemical (i.e., gossypol) in the conventional glanded (Gd) cottonseed [ 5 , 14 ]. The current strategies of valorization of cottonseed include (1) the development of novel Gl cottonseed varieties for food applications [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], (2) synthesis and formulation of biobased materials from traditional Gd cottonseed and its byproducts for nonfood applications [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], and (3) exploration of the bioactive components in cottonseed for nutritive, health, and medical applications [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. While these bioactive components are assumed to be peptide fragments, polyphenolics, and/or flavonoids, the specific functional groups or compounds are yet to be identified [ 33 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%